Seismic Evaluation and Design of Petrochemical and Other Industrial Facilities. - Facilities, Task Committee on Seismic Evaluation and Design of Petrochemical (Reston : American Society of Civil Engineers, 2020)
This report provides practical recommendations affecting the safety of new and existing petrochemical and other industrial facilities during and following an earthquake.
Reference -- Chapter 9: Post-Earthquake Damage Assessment -- 9.1 Introduction -- 9.1.1 Assessment Priorities -- 9.1.2 Assessment Triggers -- 9.2 Pre-Investigation Activities -- 9.3 Performing Field Inspections -- 9.4 Evaluation of Load-Carrying Systems -- 9.5 Identification Of Damaged Structures -- 9.6 Documentation -- 9.7 Inspection Team -- 9.8 Recommended Equipment -- References -- Chapter 10: Retrofit Design -- 10.1 Introduction -- 10.2 Upgrade Situations -- 10.3 Criteria for Voluntary Seismic Upgrading -- 10.4 Seismic Retrofit Considerations for Plant Structures and Buildings -- 10.4.1 Review of Seismic Retrofit Scheme -- 10.4.2 Seismic Retrofit Objectives -- 10.4.3 Retrofit Design Requirements and Methods -- References -- Chapter 11: New and Existing Marine oil Terminals -- 11.1 Introduction -- 11.2 Mot Descriptions -- 11.3 Historical Performance -- 11.4 State of Practice -- 11.5 Overall Approach -- 11.5.1 OLE Performance Criteria -- 11.5.2 CLE Performance Criteria -- 11.5.3 Limit State Criteria -- 11.5.4 Seismic Analysis -- 11.6 Existing Marine Oil Terminals -- References -- Chapter 12: International Codes -- 12.1 Introduction -- 12.2 Code Conformance -- 12.3 Multiple Code Conformance -- 12.4 Cautions When Performing Code Comparisons -- 12.4.1 Don't Be Fooled by the Return Period -- 12.4.2 Compare Both Capacity and Demand -- 12.4.3 Know What ``Important'' Means -- 12.4.4 Be Aware of Why -- 12.4.5 It's Not Just the Capacity and Demand That Matter -- 12.4.6 Understand the Overall Philosophy -- 12.5 Vendor Issues -- 12.6 Language Issues -- References -- Nomenclature -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Petroleum refineries-Design and construction; Electronic books